Business Strategy Sustainability of Local Product in Facing Provincial Expansion in Central Kalimantan - Kristinae, Vivy; Erwin Prasetya Toepak; Ani Mahrita; Jonathan Giovanni; Rian Sidiq Prakoso; Roby Sambung; Nurlia Eka Damayanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Research in the expansion of the Greater Kotawaringin Province was identified as meeting the administrative requirements of the number of districts, namely 5 districts consisting of East Kotawaringin, West Kotawaringin, Seruyan, Lamandau and Sukamara districts. However, the Regional Original Income in the proposed area for the expansion of Kotawaringin Raya Province is deemed unable to support sustainable regional development, especially Lamandau and Sukamara Regencies, which are the smallest contributors of all the regencies in Central Kalimantan Province, so there is a need for more monitoring and evaluation. comprehensive. The proposed expansion of the Greater Barito Province, which consists of South Barito, East Barito, North Barito and Murung Raya Regencies, is considered to still not meet administrative requirements. The proposed expansion of Barito Raya Province still consists of 4 (four) districts or one more district has not been fulfilled, so the initial recommendation that can be given is that the regional government of the Greater Barito region can add one more district or can expand the districts first. The sustainability of the business strategy is built with a vision, mission and positive influence to improve the welfare of the SMes business. The effect of entrepreneurship on innovation has an impact on SMes business performance